Análisis de la sostenibilidad y competitividad de las empresas turísticas de ocio y recreación del cantón Pangua, provincia de Cotopaxi. - Calo Quisaguano, Lida Gabriela (2023)
This research project aimed to analyze the sustainability and competitiveness of leisure and leisure tourism enterprises in the Canton of Pangua, Cotopaxi Province. Three objectives were therefore achieved in the research work. The sustainability variable was evaluated using the InnovaRSE (Navarre) method, which consists of 30 indicators divided into three dimensions: economic, social, and environmental. On the other hand, in the second objective, the competitiveness variable was measured using the BID methodology, consisting of 103 questions. From the tourist castrum of the companies of the Canton of Pangua, four companies were identified that formed the study population. The systematization of the information collected from companies was carried out using a sheet in Excel to generate descriptive statistical tables with the following results: In the variable of sustainability, there are four companies in the category of process improvement with scores between 4 and 6 due to problems in the economic, social, and environmental dimensions. About the competitiveness variable, four companies are in the range between 21% and 40% with low competitiveness because they have deficiencies in the areas mentioned. On the other hand, the correlation test was applied using the SPSS software, and result 4 was obtained. This indicates that there is no correlation between the two variables of sustainability and competitiveness in leisure and leisure tourism enterprises. In the third objective, the analysis of FODA with the matrices MEFE, MEFI, cross-cross, impact assessment, and strategies were carried out, where 16 improvement strategies were analyzed and proposed, agreements were made, systems were implemented, a training program was created, etc. In conclusion, by proposing improvement strategies, companies can compete and have greater growth at the local and national levels.